Metagenomic analysis reveals that activated carbon aids anaerobic digestion of raw incineration leachate by promoting direct interspecies electron transfer. (15th September 2019) - Lei, Yuqing; Sun, Dezhi; Dang, Yan; Feng, Xianlu; Huo, Da; Liu, Chuanqi; Zheng, Kun; Holmes, Dawn E.
Abstract: The raw fresh leachate from municipal solid waste (MSW) incineration plants contains high concentrations of volatile fatty acids (VFAs), ammonia and metals, all compounds that severely limit anaerobic digestion treatment efficiencies. These inhibitory compounds make reactor systems unstable, causing reactor start-up periods to take more than 100 days, even when the leachate is diluted significantly. In this study, granular activated carbon (GAC) was incorporated into a bioreactor fed with raw incineration leachate. Addition of GAC allowed direct treatment of raw incineration leachate without any start-up acclimation period, while the non-amended control reactor soured immediately and collapsed within 17 days. When hydraulic retention time (HRT) of the GAC-amended reactor was stepwise decreased to increase organic loading rates (OLR) to 25.0 kgCOD/(m 3 ·d), COD removal efficiencies remained stable at >90%. Metagenomic analysis of the GAC-amended reactor revealed that Geobacter and Methanosarcina, species known to participate in direct interspecies electron transfer (DIET), were more abundant in the GAC-amended reactor than the seed sludge. In addition, the abundance of genes coding for proteins thought to be involved in DIET such as electrically conductive pili and the outer membrane c -type cytochrome, OmcS, increased significantly, while genes involved in fermentation, and nitrate ( narG ) and sulfate ( dsrA ) reduction dropped significantly as the experiment progressed. These results are significant because this is the first detailed investigation into the metabolic capabilities of microbial communities involved in efficient treatment of raw incineration leachate within biomethanogenic reactors that did not require a long start-up period. Graphical abstract: Image 1 Highlights: GAC dosing facilitated direct and efficient treatment of raw incineration leachate. GAC dosing allowed UASB reactor to operate stably under high organic loading rates. GAC stimulated the growth of methanogens and insoluble metal reducing bacteria. GAC enriched Methanosarcina and Geobacter species that can participate in DIET. GAC increased the number of Geobacter pilA and omcS gene copies.